Macrophage galactose-type lectin (MGL) is induced on M2 microglia and participates in the resolution phase of autoimmune neuroinflammation - Ilarregui, Juan M. (J Neuroinflammation, 2019)
BACKGROUND: Multiple sclerosis (MS) involves a misdirected immune attack against myelin in the brain and spinal cord, leading to profound neuroinflammation and neurodegeneration. While the mechanisms of disease pathogenesis have been widely studied, the suppression mechanisms that lead to the resolution of the autoimmune response are still poorly understood. Here, we investigated the role of the C-type lectin receptor macrophage galactose-type lectin (MGL), usually expressed on tolerogenic antigen-presenting cells (APCs), as a negative regulator of autoimmune-driven neuroinflammation. METHODS: We used in silico, immunohistochemical, immunofluorescence, quantitative real-time polymerase chain reaction (qRT-PCR) and flow cytometry analysis to explore the expression and functionality of MGL in human macrophages and microglia, as well as in MS post-mortem tissue. In vitro, we studied the capacity of MGL to mediate apoptosis of experimental autoimmune encephalomyelitis (EAE)-derived T cells and mouse CD4(+) T cells. Finally, we evaluated in vivo and ex vivo the immunomodulatory potential of MGL in EAE. RESULTS: MGL plays a critical role in the resolution phase of EAE as MGL1-deficient (Clec10a(−/−)) mice showed a similar day of onset but experienced a higher clinical score to that of WT littermates. We demonstrate that the mouse ortholog MGL1 induces apoptosis of autoreactive T cells and diminishes the expression of pro-inflammatory cytokines and inflammatory autoantibodies. Moreover, we show that MGL1 but not MGL2 induces apoptosis of activated mouse CD4(+) T cells in vitro. In human settings, we show that MGL expression is increased in active MS lesions and on alternatively activated microglia and macrophages which, in turn, induces the secretion of the immunoregulatory cytokine IL-10, underscoring the clinical relevance of this lectin. CONCLUSIONS: Our results show a new role of MGL-expressing APCs as an anti-inflammatory mechanism in autoimmune neuroinflammation by dampening pathogenic T and B cell responses, uncovering a novel clue for neuroprotective therapeutic strategies with relevance for in MS clinical applications. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12974-019-1522-4) contains supplementary material, which is available to authorized users.